1999
DOI: 10.1105/tpc.11.5.901
|View full text |Cite
|
Sign up to set email alerts
|

Plastid Translation Is Required for the Expression of Nuclear Photosynthesis Genes in the Dark and in Roots of the Pea lip1 Mutant

Abstract: The expression of nuclear photosynthesis genes in pea seedlings requires both light and a postulated signal produced by developing plastids. The requirement for the plastid signal for the accumulation of transcripts of Lhcb1, RbcS, PetE, and AtpC genes was investigated in the pea mutant lip1, which shows light-independent photomorphogenic development. Lincomycin and erythromycin, inhibitors of plastid translation, decreased the accumulation of transcripts of nuclear photosynthesis genes in shoots of light-grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
73
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(82 citation statements)
references
References 43 publications
(52 reference statements)
6
73
1
Order By: Relevance
“…HY5 binds ACGT-containing promoter elements, for example the G box, and contributes to numerous light-regulated processes [50]. The idea that these findings are explained by cry1 attenuating 1 O 2 -dependent plastid-to-nucleus signalling [29] conflicts with the findings that cry1 and hy5 were gun mutants when chloroplast biogenesis was blocked with lincomycin treatments [5], which do not require light to block plastid development [48], and that cry1 and hy5 mutants are more sensitive to excess light than wild-type [5]. Chloroplasts also appear to affect light signalling mediated by cry2 and phytochrome A [51].…”
Section: Integration Of Light and Plastid-to-nucleus Signallingcontrasting
confidence: 46%
See 1 more Smart Citation
“…HY5 binds ACGT-containing promoter elements, for example the G box, and contributes to numerous light-regulated processes [50]. The idea that these findings are explained by cry1 attenuating 1 O 2 -dependent plastid-to-nucleus signalling [29] conflicts with the findings that cry1 and hy5 were gun mutants when chloroplast biogenesis was blocked with lincomycin treatments [5], which do not require light to block plastid development [48], and that cry1 and hy5 mutants are more sensitive to excess light than wild-type [5]. Chloroplasts also appear to affect light signalling mediated by cry2 and phytochrome A [51].…”
Section: Integration Of Light and Plastid-to-nucleus Signallingcontrasting
confidence: 46%
“…These composite elements are composed of at least two common promoter elements [1,16,18]. Light and plastid signals appear distinct because plastid signals can regulate PhANG expression in the dark [5,19,48]. Plastid-to-nucleus signalling that is activated by chloroplastic ROS uses distinct promoter elements from those activated by blocking chloroplast biogenesis with norflurazon treatments [46].…”
Section: Integration Of Light and Plastid-to-nucleus Signallingmentioning
confidence: 99%
“…In land plants, inhibition of chloroplast protein synthesis leads to decreased accumulation of transcripts of nuclear genes encoding proteins involved in photosynthesis (Sullivan and Gray, 1999). To test whether a similar decline occurs in C. reinhardtii upon repression of chloroplast transcription and translation, the mRNA levels of several photosynthetic proteins were determined by quantitative RT-PCR (qRT-PCR) (Figure 8).…”
Section: Conditional Inactivation Of Chloroplast Transcription and Trmentioning
confidence: 99%
“…However, recent experimental work goes some way to clarifying this 291 question. Supporting the early study by Sullivan and Gray (Sullivan and Gray, 1999) the work 292 of Martín et al (2016) demonstrated that the inhibitory effect of lincomycin blocks the 293 photomorphogenic responses early and rapidly, indicating that the retrograde signal is already 294 present in the proplastids/etioplasts, or is developed rapidly in response to defective chloroplasts 295 in order to prevent normal development in light. The results from the experiments by Martín et 296 al.…”
mentioning
confidence: 64%
“…Early research 272 provided strong indications that a plastid retrograde signal is required for full expression of the 273 nuclear-encoded photosynthetic genes (Sullivan and Gray, 1999). Blocking PEP-driven plastid 274 transcription with rifampicin or using mutants of various PEP components blocked PhANG 275 expression in a light-independent way (Woodson et al, 2013).…”
mentioning
confidence: 99%